Sri Lanka : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper on Sri Lanka underlies the dynamics of growth and external competitiveness. The slowdown in the contribution of sectors that are labor intensive, together with faster growth in sectors that are capital intensive and have higher productivity levels, resulted in total factor productivity (TFP) as the main contributor to growth. Sri Lanka's strong growth performance has brought positive benefits to the economy and has benefited from a high quality labor force. The labor productivity is low by regional standards and the internal terms of trade are skewed toward the nontraded sector.